The construct validity of a traditional 25m test of swimming competence - Junge, M.; Blixt, T.; Stallman, R. K. (Biomechanics and Medicine in Swimming XI, 2010)
A universal definition of the ability to swim has yet to be agreed upon. Some believe that "how far" one swims is the most important criterion. The number of meters is controversial. Some use a traditional definition of from 25m to 200m, often as the only criterion of "can swim". In fact, this is not the point. A conceptual model emphasizes broader competence. The result of this model is a combined test including more than only distance. This combined test was used as the criterion to test the construct validity of a traditional test. When these two tests were compared they were found to be very different, thus measuring different qualities. Among children already declared able to swim by the traditional test, only 5.7% satisfied the conditions of the conceptual test. It was concluded that the traditional test was not a valid measure of the ability to swim.